Analysis of Charterparty Agreements from Textual Genre and Translation Points of View - Del Pozo Triviño, Maribel (Meta, 2014)
Maritime transportation in the world today accounts for huge turnover figures and it provides sizeable commercial activity of a multicultural and multilingual nature. Most of these transactions are carried out in English, and consequently, it is not surprising that such activity generates a large amount of translation work, especially from English into other languages. One of the maritime legal documents that frequently requires translation is the Charterparty, an agreement that enables a ship-owner to charter his vessel to another party for a certain consideration. This paper focuses on the analysis of the Charterparty Agreement from a translation point of view. First, we will describe the analysis method, which is based on the concept of textual genre, and then we will proceed to a detailed analysis of the Charterparty Agreement.